2010
DOI: 10.1007/s12028-010-9411-9
|View full text |Cite
|
Sign up to set email alerts
|

QTc Interval and Neurological Outcomes in Aneurysmal Subarachnoid Hemorrhage

Abstract: This study confirms that QTc interval prolongation continues in the SAH patients with an unfavorable outcome but that QTc interval prolongation improves in patients with a good outcome, suggesting that a QTc interval of more than 448 ms at 7 days after operation is a predictor of neurological outcome after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The presence of prolonged QTc interval was associated with a five-times-increased risk of death in SAH patients, compared to those with normal QTc interval. This concurs with the previous studies that evaluated prolonged QTc interval prognostic significance [7, 8]. Ichinomiya et al reached a conclusion similar to ours; however, they used the Glasgow Outcome Scale at hospital discharge, as a primary outcome, rather than in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The presence of prolonged QTc interval was associated with a five-times-increased risk of death in SAH patients, compared to those with normal QTc interval. This concurs with the previous studies that evaluated prolonged QTc interval prognostic significance [7, 8]. Ichinomiya et al reached a conclusion similar to ours; however, they used the Glasgow Outcome Scale at hospital discharge, as a primary outcome, rather than in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Ichinomiya et al reached a conclusion similar to ours; however, they used the Glasgow Outcome Scale at hospital discharge, as a primary outcome, rather than in-hospital mortality. They found that a QTc of 448 ms at day 7 of admission was 73% sensitive (95% CI 68–78%) and 93% specific (95% CI 90–96%) prognostic tool to detect such outcome [7]. Marafioti et al reported that prolonged QTc was an independent prognostic tool for detection of index mortality in SAH patients when it was compared to other prognostic risk factors such as clinical and CT grading of SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these analyses suggested that only female sex and hypokalemia were an independent risk factor for severe QTc prolongation in SAH patients [66]. It has been confirmed that QTc interval prolongation improved in patients with a good prognosis; it persisted in SAH patients with a poor outcome, further indicating that a QTc interval of longer than 448 ms at 7 days after surgery can serve as a predictor of clinical outcome following SAH [67]. Twenty-three patients with SAH were examined, who showed an ST segment elevation in their ECG [68].…”
Section: Manifestations Of Nonneurologic Complications After Sahmentioning
confidence: 99%
“…21 The association in the current study between prolonged QT interval and angiographic vasospasm may explain the findings of Ichinomiya and colleagues who found that a prolonged QT interval (Ͼ448 ms) at 7 days postaneurysm rupture was a predictor of neurological outcome. 35 This group furthermore found that improvement in QT prolongation was associated with favorable outcome, suggesting a role for angiographic vasospasm as a mechanistic explanation. A significant limitation of previous studies is the lack of assessment of angiographic data to diagnose vasospasm.…”
Section: Discussionmentioning
confidence: 96%